2021
DOI: 10.1002/chem.202100832
|View full text |Cite
|
Sign up to set email alerts
|

Trifaceted Mickey Mouse Amphiphiles for Programmable Self‐Assembly, DNA Complexation and Organ‐Selective Gene Delivery

Abstract: Instilling segregated cationic and lipophilic domains with an angular disposition in a trehalose-based trifaceted macrocyclic scaffold allows engineering patchy molecular nanoparticles leveraging directional interactions that emulate those controlling self-assembling processes in viral capsids. The resulting trilobular amphiphilic derivatives, featuring a Mickey Mouse architecture, can electrostatically interact with plasmid DNA (pDNA) and further engage in hydrophobic contacts to promote condensation into tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…34 Further on, α,α'-trehalose-based macrocycles (cyclotrehalans, CTs) were found to undergo co-assembly with plasmid DNA (pDNA) to afford transfectious nanocomplexes (CTplexes) with organ-selective gene delivery capabilities. 35…”
Section: Introductionmentioning
confidence: 99%
“…34 Further on, α,α'-trehalose-based macrocycles (cyclotrehalans, CTs) were found to undergo co-assembly with plasmid DNA (pDNA) to afford transfectious nanocomplexes (CTplexes) with organ-selective gene delivery capabilities. 35…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we focused on the development of polycationic amphiphilic trehalose derivatives with Siamese and Janus-macrocyclic structure (cyclotrehalans, CTs) . These terms refer specifically to α,α′-trehalose-based amphiphiles, which are symmetrical , or cyclic structures formed from α,α′-trehalose (a nonreducing sugar composed of two linked glucose molecules). These structures have been studied for their ability to undergo coassembly with plasmid DNA (pDNA) to form transfection complexes.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that macrocycles built from the disaccharide α , α ’‐trehalose (cyclotrehalans, CTs) represent an appealing alternative to CDs. [ 12 ] Differently from CDs, CTs depict a convex inner hydrophobic cavity flanked by secondary hydroxyls that project from concave faces. [ 13 ] In principle, this architecture must facilitate the access of size‐fitting guests to the cavity even if relatively bulky O ‐substituents are present.…”
Section: Introductionmentioning
confidence: 99%